A Review of Prosopis Cineraria as Hepatoprotective - Shruti, Saini; Divya, Singh; Surbhi, Jangir; Sharma, Rakesh (Journal of Biomedical and Pharmaceutical Research, 2024)
Abstract: Prosopis cineraria (L.) Druce is known as Ghaf and is a member of the Mimosoideae subfamily of the Leguminosae family. The plant affects people’s life in sociological, ethnological, traditional, and therapeutic ways. The goal is to highlight the plant’s potential for bioactivity while offering a comprehensive summary of the most recent studies. The review’s objectives were to provide a comprehensive tabulation of the data in a style that would be useful to academic researchers and to update the data on therapeutic actions that had been published in scientific journals. To ascertain the phytochemical components of the leaf, stem, pod, and bark as well as their safety and pharmacological details, a comprehensive scientific study of P. cineraria (L.) was carried out. The review helps identify future opportunities and limitations in the field by using the condensed scientific information of P. cineraria (L.). Keywords: Phytochemical, Pharmacological, Leguminosae, Ghaf, Prosopis Cineraria